The Influence of Work-Life Balance and Job Satisfaction on Organizational Commitment through Work Motivation among Employees and Health Cadres of UPTD Cikembar Public Health Center, Sukabumi Regency - Ferry Priantono (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the effect of work-life balance and job satisfaction on organizational commitment, with work motivation as an intervening variable among employees of UPTD Puskesmas Cikembar, Sukabumi Regency. This research employed a quantitative approach with a causal associative design. The population consisted of 580 active employees and health cadres at UPTD Puskesmas Cikembar. The sample size was determined using the Slovin/Yamane formula with a 5% margin of error, resulting in 237 respondents. The sampling technique used was proportional stratified random sampling. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that work-life balance has a positive and significant effect on work motivation. Job satisfaction also has a positive and significant effect on work motivation. Furthermore, work-life balance, job satisfaction, and work motivation have positive and significant effects on organizational commitment. The mediation test shows that work motivation mediates the effect of work-life balance and job satisfaction on organizational commitment. These findings confirm that strengthening organizational commitment among public health center employees is not only determined by work-life balance and job satisfaction but also by the organization’s ability to enhance employee work motivation. The practical implication of this study suggests that Puskesmas management should strengthen work-life balance policies, improve job satisfaction across employment statuses, and create a work climate that promotes motivation and employee loyalty.